TandT Music Pioneers Honoured in New York - Ashby, Glenville (Guardian)
Austin Stoker and Michael Alexander were recognised and honoured in Brooklyn for their sacrifice and contribution to the Caribbean art form. As members of a trio they made a historic appearance with a three piece steelband in the 1954 Broadway musical production, House of Flowers which was one of the early highlights for steel band music in New York.
Keywords: Musicians -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago -- History; Steel band music -- Trinidad and Tobago; Award presentations